2019
DOI: 10.1093/femsec/fiz198
|View full text |Cite
|
Sign up to set email alerts
|

Genomic and gene expression evidence of nonribosomal peptide and polyketide production among ruminal bacteria: a potential role in niche colonization?

Abstract: Genomic and transcriptomic analyses were performed to investigate nonribosomal peptide synthetases (NRPS) and polyketide synthases (PKS) in 310 genomes of ruminal/fecal microorganisms. A total of 119 biosynthetic genes potentially encoding distinct nonribosomal peptides (NRPs) and polyketides (PKs) were predicted in the ruminal microbial genomes and functional annotation separated these genes into 19 functional categories. The phylogenetic reconstruction of the 16S rRNA sequences coupled to the distribution of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 64 publications
2
7
0
Order By: Relevance
“…The genes considered essential to lasso peptide biosynthesis showed a low level of expression in the ruminal metatranscriptome datasets and were more expressed within the microbial community of the sheep rumen, which is in agreement with our previous observations indicating that non-ribosomal peptide synthetases (NRPS) and polyketide synthases (PKS) were also more abundant in the rumen microbiota of sheep (Moreira et al, 2020). Additionally, the reads corresponding to the genes found in Butyrivibrio sp., Lachnospira sp., and Ruminococcus sp.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The genes considered essential to lasso peptide biosynthesis showed a low level of expression in the ruminal metatranscriptome datasets and were more expressed within the microbial community of the sheep rumen, which is in agreement with our previous observations indicating that non-ribosomal peptide synthetases (NRPS) and polyketide synthases (PKS) were also more abundant in the rumen microbiota of sheep (Moreira et al, 2020). Additionally, the reads corresponding to the genes found in Butyrivibrio sp., Lachnospira sp., and Ruminococcus sp.…”
Section: Discussionsupporting
confidence: 91%
“…Additionally, the reads corresponding to the genes found in Butyrivibrio sp., Lachnospira sp., and Ruminococcus sp. were most represented in the sheep metatranscriptomes, also confirming previous observations showing a higher prevalence of NRPS and PKS within members of these ruminal taxa (Moreira et al, 2020). Taken together, these results demonstrate the potential production of antimicrobial compounds by species of bacteria colonizing the rumen of sheep, which deserves further investigation.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In contrast, we showed that expression of non-ribosomally synthesised peptides and polyketide increased during secondary colonisation within fresh PRG attached bacteria [81]. The DE of these ribosomally and non-ribosomally synthesised AMPs and polyketides during the transition from primary to secondary colonisation may well contribute towards the antagonism between the bacteria characteristic of the two phases of PRG colonisation.…”
Section: Discussionmentioning
confidence: 65%